2014
DOI: 10.1103/physrevb.89.214508
|View full text |Cite
|
Sign up to set email alerts
|

Charge transport in InAs nanowire Josephson junctions

Abstract: We present an extensive experimental and theoretical study of the proximity effect in InAs nanowires connected to superconducting electrodes. We fabricate and investigate devices with suspended gate-controlled nanowires and nonsuspended nanowires, with a broad range of lengths and normal-state resistances. We analyze the main features of the current-voltage characteristics: the Josephson current, excess current, and subgap current as functions of length, temperature, magnetic field, and gate voltage, and compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
73
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 47 publications
12
73
2
Order By: Relevance
“…For instance, the coupling of gate-defined qubits at the nanowire ends via a superconductor has been proposed 2 , but also quantum network structures 5 . Further, gateable nanowire-based Josephson junctions [6][7][8] are in the focus of ongoing research. SC/InAs systems have been predicted to provide the optimal environment for proximity-induced p-wave superconductivity, leading in presence of an external magnetic field to spinless quasiparticles in form of triplet state Cooper pairs within the semiconductor 4,9 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the coupling of gate-defined qubits at the nanowire ends via a superconductor has been proposed 2 , but also quantum network structures 5 . Further, gateable nanowire-based Josephson junctions [6][7][8] are in the focus of ongoing research. SC/InAs systems have been predicted to provide the optimal environment for proximity-induced p-wave superconductivity, leading in presence of an external magnetic field to spinless quasiparticles in form of triplet state Cooper pairs within the semiconductor 4,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Owing to these excellent material characteristics and their intrinsic low dimensionality, InAs and InP nanowires have been explored to realize various novel devices and systems, including nanowire field-effect transistors, [1][2][3][4] light emitting devices, [5,6], solar cells, [7][8][9] and superconducting quantum devices. [18][19][20][21] It has also been demonstrated that InAs nanowires exhibit strong electron spin-orbit coupling and these nanowires are desired materials for realization of topological superconducting systems in which Majorana bound states can be present and exploited for topological quantum computation. [22][23][24][25][26][27] Epitaxially grown InAs and InP nanowires can have zincblende lattice structures and are most commonly oriented along 111 crystallographic directions.…”
Section: Introductionmentioning
confidence: 99%
“…S. Abay and coworkers in Ref. 34 suggested an alternative mechanism based on the presence of inhomogeneities in the NW. In this scenario, the observed peaks would be related to the sequential appearance of normal domains in the NW as the current is increased.…”
Section: Eletrical Transport Measurementsmentioning
confidence: 99%